An independent practitioner's introduction to child and adolescent psychotherapy : playing with ideas - Dowling, Deirdre (Independent psychoanalytic approaches with children and adolescents, 2019)
An Independent Practitioner's Introduction to Child and Adolescent Psychotherapy: Playing with Ideas is a comprehensive guide to child and adolescent psychotherapy, taking the practitioner from the initial meeting through the therapeutic process with young people of different ages, to the ending of psychotherapy. It includes approaches to working with parents and the family, introduces theoretical ideas simply and provides references for further learning. Part of the popular Independent Psychoanalytic Approaches series, this book is written from an Independent perspective, but it is also an account of Deirdre Dowling's approach, developed from her considerable experience of working in the NHS and now as a private practitioner. An Independent Practitioner's Introduction to Child and Adolescent Psychotherapy will be an indispensable guide for child psychotherapists (especially trainees), colleagues working in child and family mental health settings, play therapists, counsellors and support staff in schools and child care professionals working therapeutically in residential and community settings.